How South Korea Represents Japan as Colonization in Film - Azhari; Cristian Zamir Sierra Echeverria; Muhammad Zikrullah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
The advancement of the movie industry makes it undeniable that wars between countries have occurred until now. It's just that the way of fighting is different. This study can conceptually illustrate the strategy of a country to attack another country by reconstructing the country's image negatively. The purpose of this study is to understand the representation of Japan as a colonizer in a Korean film entitled "Exhuma." This study employed a qualitative research design. The Exhuma film's symbol analysis research requires a wide range of data sources to support the interpretation of its meaning and messages. The primary source of data is the Exhuma film, where the researcher thoroughly examines the symbol elements to determine which symbols are there. The data is analyzed in seven stages: identification of symbols, analysis of literal meaning, relationship of symbols with context, consideration of interpretation, strengthening interpretation with supporting evidence, relationship of interpretation with themes, and drawing conclusions about the findings. Based on the results of the data analysis, it was found that in the film Exhuma, Japan is represented as a colonizer with two categories of historical and mythical symbols. Historical symbols are signs or symbols that depict the atrocities of Japanese colonization, based on adaptations of historical facts. While mystical symbols are signs or symbols that represent the atrocities of Japanese colonization based on supernatural or mystical beliefs and myths in the beliefs and culture of South Korean society.